The Analysis of Gas Balloon Supply Systems - P.R.Fayziyev; I.A.Ikromov; N.I.Otaboyev; A.A.Abduraximov (Genius Journals, 2022)
Gas engines are widely used in modern urban vehicles. It uses compressed or liquefied natural, industrial and synthetic gases. The basic scheme of the gas supply system, the order of operation and requirements to them, and the advantages and disadvantages of the system are discussed.
Keywords: Gas Cylinder Engines; Gaseous Fuel; Gas Cylinders; Reducer